Comparative study of costs in the treatment of prostate cancer Naval Medical Center, 2008-2011 - Quevedo, Oscar (2020)
The pharmacological treatment with biological drugs for oncological diseases means a high investment for Peru, for this reason, it is of the utmost importance to rationally use the resources by conducting the various pharmaco-economic studies that exist. The objective was to determine and compare the cost-effectiveness ratio of leuprolide acetate 7.5 mg and goserelin 3.6 mg in Naval Medical Center “Surgeon Major Santiago Távara”, Lima, Peru. It is a pharmacoepidemiological study of a pharmaco-economic nature. Analytical, retrospective design. The medical records of 46 patients diagnosed with prostate cancer during the period from January 2008 to December 2011, who were prescribed one of the study drugs were reviewed and analyzed. The effectiveness, average cost of cancer therapy per patient and cost-effectiveness were determined. The information was processed using the statistical program SPSS version 22, obtaining frequencies, means, standard deviation, standard error and coefficient of variation and inferential (t student) with 95 % confidence interval, p<0.05. It was found high effectiveness expressed as a percentage reduction in prostate specific antigen, 85.84 % with leuprolide acetate and 90.72 % with goserelin, a difference that was not statistically significant (p>0.05). The drug that obtained the lowest cost-effectiveness ratio by percentage reduction of prostate specific antigen was gosereline (S/. 73.69) compared with leuprolide acetate (S/. 155.27). It was concluded that the most estimate cost-effective alternative in the treatment of prostate cancer at the Naval Medical Center during the period from January 2008 to December 2011 was goserelin.